2018
DOI: 10.18261/issn.0805-9535-2018-04-02
|View full text |Cite
|
Sign up to set email alerts
|

Fra deadline til flowline

Abstract: Fra deadline til flowline En trinn for trinn-analyse av endring i en norsk medieorganisasjon From deadline to flowline A step-for-step analysis of change in a Norwegian media organization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Even though the introduction of online publishing as well as content management systems demanded the journalists change their working routines, several observers point out that media organisations are rather slow in innovation (Steensen 2009;Wurff and Lauf 2005). Hagen, Tolstad, and Bygdås (2018) report their action research in one of the Amedia newspapers (Moss Avis) where they observed and facilitated what they call a change "from deadline to flowline", indicating that the newsroom was essentially directed towards print as recently as 2017.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though the introduction of online publishing as well as content management systems demanded the journalists change their working routines, several observers point out that media organisations are rather slow in innovation (Steensen 2009;Wurff and Lauf 2005). Hagen, Tolstad, and Bygdås (2018) report their action research in one of the Amedia newspapers (Moss Avis) where they observed and facilitated what they call a change "from deadline to flowline", indicating that the newsroom was essentially directed towards print as recently as 2017.…”
Section: Discussionmentioning
confidence: 98%
“…Today the conglomerate is important for innovation in local media in this group as head office provides analytical services an individual newspaper could not afford. The head office also serves as a hub for spreading news ideas among the newspapers so successful innovations in one of the local newspapers can be transferred to others, such as the successful shift from print first to online first that Hagen et al (2018) described.…”
Section: Discussionmentioning
confidence: 99%
“…The background for this change is that the newspapers are moving away from a business model based on a 70/30 distribution of advertisement and subscription revenues, toward what the industry calls “digital first” (Singer, 2018). Roughly, this means that the digital version of newspapers shall control the priorities and strategies of the newspapers, as well as being the employees’ main focus all the time (Hagen et al., 2018).…”
Section: Empirical Analysismentioning
confidence: 99%